(untitled) (Journal of Education and Development, 2025)
Medical school educators are tasked with the responsibility of teaching medical students how to take relevant medical histories from patients and develop communication and interpersonal skills. In this ethically approved undergraduate medical teaching programme, the authors used body-maps to extend and expand the traditional history taking skills taught to medical students. This paper details the body-map methodology and the enthusiastic feedback from the medical students. In addition to the enhancement of their history taking skills, the students reported how improved self-awareness and self-reflection from the body-map programme gave them the confidence to develop empathic relationships with one another and their patients.